Protocol for a prospective cohort study: Prevention of Transmissions by Effective Colonisation Tracking in Neonates (PROTECT-Neo) - Martin Wolkewitz; Roland Hentschel; Philipp Henneke; Daniel Jonas; Tim Götting; Sandra Reuter; Daniel Klotz; Simone Hock; Benjamin Blümel; Georg Häcker; Hajo Grundmann; Nico Mutters (BMJ Open)
Introduction Transmissions of opportunistic bacterial pathogens between neonates increase the risk of infections with negative repercussions, including higher mortality, morbidity and permanent disabilities. The probability of transmissions between patients is contingent on a set of intrinsic (patient-related) and extrinsic (ward-related) risk factors that are not clearly quantified. It is the dual objective of the Prevention of Transmissions by Effective Colonisation Tracking-Neo study to determine the density of transmission events in a level III neonatal intensive care unit (NICU) and to identify risk factors that may be causally associated with transmission events.Methods and analysis A full cohort of patients treated in a 17-bed level III NICU will be prospectively followed and transmission events between two or more patients will be documented. A transmission event occurs when isogenic isolates from two different patients can be identified. Isolates will be obtained by routine weekly screening. Isogenicity will be determined by whole-genome sequencing. During the study, relevant intrinsic and extrinsic risk factors will be recorded. Specimen and data will be collected for 1 year. We postulate that transmission density increases during episodes when demand for intensive care cannot be met by existing staff, and that threshold dynamics have a bearing on cohorting and hand hygiene performance. Poisson logistic regression, proportional hazard and multilevel competing risk models will be used to estimate the effect of explanatory variables.Ethics and dissemination This study has been approved by the local ethics committee (study ID 287/18). The results will be published in peer-reviewed medical journals, communicated to participants, the general public and all relevant stakeholders.Trial registration number The German Clinical Trials Registry (DRKS00017733); Pre-results.